2021
DOI: 10.1101/2021.08.20.21261620
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

IgA deficiency destabilizes immunological homeostasis towards intestinal microbiota and increases the risk of systemic immune dysregulation

Abstract: Mammals produce large quantities of mucosal and systemic antibodies that maintain the intestinal barrier, shape the intestinal microbiome and promote lifelong mutualism with commensal microbes. Here, we developed an integrated host-commensal approach combining microbial flow cytometry and 16s rRNA gene sequencing to define the core microbes that induce mucosal and systemic antibodies in pediatric selective Immunoglobulin A (IgA) deficient and household control siblings with CyTOF analysis to determine the impa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 50 publications
0
11
0
Order By: Relevance
“…Here we show that a large portion of the trout gut microbiota is double-coated by sIgT and sIgM, while the largest proportion is sIgT single coated, being the smallest percentage single sIgM coated. Interestingly, two reports have shown that the human gut microbiota follows a similar pattern of coating with sIgA and sIgM double-coated microbiota being the most prevalent coating mode (5,18), while in another human study they reported different proportions of sIgA/sIgM coating (19). Among many other possibilities, it is likely that such differences in gut sIg microbiota coating in humans are due to methodological methods in the assessment of sIg coating, or the use of different human cohorts with very different genetic backgrounds.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Here we show that a large portion of the trout gut microbiota is double-coated by sIgT and sIgM, while the largest proportion is sIgT single coated, being the smallest percentage single sIgM coated. Interestingly, two reports have shown that the human gut microbiota follows a similar pattern of coating with sIgA and sIgM double-coated microbiota being the most prevalent coating mode (5,18), while in another human study they reported different proportions of sIgA/sIgM coating (19). Among many other possibilities, it is likely that such differences in gut sIg microbiota coating in humans are due to methodological methods in the assessment of sIg coating, or the use of different human cohorts with very different genetic backgrounds.…”
Section: Discussionmentioning
confidence: 98%
“…Our follow-up studies on fish sIgT demonstrated that control of microbiota homeostasis by sIgs is a primordial function of specialized mucosal sIgs already found in early vertebrates such as teleosts ( 10 ). However, the current dogma that sIg-dependent microbiota homeostasis is mediated by sIgA or sIgT in vertebrates, has recently been challenged by several studies showing that significant proportions of human and fish microbiota are coated by sIgM in the gut and other mucosal surfaces ( 5, 18, 19 ). Because sIgM does not coat the microbiota of mice under either specific-pathogen-free (SPF) or non-SPF conditions ( 5, 7 ), laboratory mouse models to study the potential role of sIgM in host-microbiome interactions are not suitable to address this question.…”
Section: Discussionmentioning
confidence: 99%
“…IgA is known to control mucosal pathogens 1214 , but the impact of IgA on inflammatory diseases and malignancy remains unclear. Recent studies have indicated that IgA deficiency is associated with changes in microbiota and systemic inflammation 4,6,7,15 , which may be more pronounced in patients with undetectable IgA 8 . A compensatory increase in the other major secreted antibody isotype, IgM, is insufficient to rescue these effects 4 .…”
Section: Mainmentioning
confidence: 99%
“…IgA prevents microbial translocation and related immune dysregulation, leading to milder symptoms in SIgAD patients. 190 Furthermore, a study underscores commensal bacteria's impact on serum IgA levels, emphasizing T cell-dependent systemic responses. It links microbiota composition to serum IgA concentrations and identifies protective roles against sepsis when using mFLOW-Seq for microbiota analysis.…”
Section: Microbial Flow Cytometry Coupled To Ngs (Mflow-seq)mentioning
confidence: 99%